Recent global patterns in skin cancer incidence, mortality, and prevalence - Mingyue Wang; Xinghua Gao; Li Zhang; Lishao Guo; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Background:. Skin cancer is a common skin disease whose incidence and mortality rates have been showing yearly increases. In this report, we update the most recent data on skin cancer as obtained from GLOBOCAN 2022. Methods:. The incidence and mortality rates of skin cancer (melanoma of skin and non-melanoma skin cancer) in GLOBOCAN 2022 were reviewed. These data were analyzed and the characteristics of incidence and mortality across five continents and top five countries and regions in each continent are presented. In addition, correlations between Human Development Index (HDI) and age-standardized incidence and mortality rates of these two skin cancers are described. Results:. The GLOBOCAN 2022 data indicated that melanoma was the 17th most common cancer. An estimated 331,722 people were diagnosed with melanoma globally and approximately 58,667 died from this disease. For non-melanoma skin cancer, it ranks as the 5th most common cancer, and an estimated 1,234,533 people were diagnosed with non-melanoma skin cancer globally and approximately 69,416 died from this disease. The incidence of skin cancer varies across geographic regions and countries, with a predominance observed in Oceania, North America, and Europe. Australia was ranked first in terms of incidence, while incidence rates in Africa and Asia were very low. Despite these regional differences in incidence, there was little geographic variation in mortality rates. Currently, the number of deaths from non-melanoma skin cancer exceeds that of melanoma of skin. HDI was positively associated with the incidence of both types of skin cancers, with a positive correlation obtained between HDI and mortality from melanoma of skin and a negative correlation between HDI and mortality from non-melanoma skin cancer. Conclusions:. Skin cancer remains a major disease burden worldwide. Substantial variations are observed across countries and regions. Further research on skin cancer will be required to provide a rationale for more effective preventions and treatments of this condition.